Efeitos de 12 semanas de treinamento físico com Exergames de dança no estado de humor e aptidão funcional de mulheres idosas - Santos, Rafaela Gomes dos (2021)
The mood is a transitory feeling state with variable intensities that influence the sense of wellbeing and active aging involves a set of habits and positive attitudes that contribute to improvements in mental and functional conditions in the elderly. Interventions based on Exergames, associated with the aging process can favor mental and physical health. However, most studies focus on balance and functional mobility. The present study aimed to evaluate the effects of a 12-week training program with Dance Exergames on the Xbox 360 on the mood and functional fitness profile of elderly women. For this purpose, volunteers aged ≥ 60 years who participated in a physical activity program for the elderly in the municipality of Teixeira de Freitas (BA) were recruited. Physically inactive women, not participating in the Physical Activity Program, were recruited to compose the control group and were not submitted to any type of physical training. The sample (n=22) was divided into Exergames Group (EG, n=9, 70.6 ± 1.6 years) and Control Group (CG, n=13, 73.6 ± 2.2 years). Evaluations were carried out before and after the interventions, and each participant played, in pairs, the electronic game Dance Central 3, with the XBOX 360 Kinect console (Slim, Microsoft, USA). The EG trained for 12 weeks (24 sessions), with two weekly sessions of 50 minutes and the CG performed manual activities workshops. To assess the profile of mood and functional fitness, the POMS (Profile of Mood States) and the Senior Fitness Test (SFT) questionnaires were applied, respectively. Data analysis was performed using the SPSS 23 statistical package (Statistical Package for the Social Sciences). Therefore, data normality was tested using the Shapiro-Wilk test, and pre-and post-intervention fun and affectivity were assessed using the Wilcoxon test. To assess the effect of time, intervention, and interaction (time*group), an application of generalized models, the Generalized Mixed Model (GMM), with unstructured covariance matrix and Bonferroni's post hoc test was used. The subjective perception of effort, during the 12 weeks, was 10.1±2.4 (training intensity perceived as light, on average) and fun and affectivity did not change throughout the training. About functional fitness, both the exercise training with exergame (EG) and the intervention model for the CG did not produce significant effects regarding the interaction (group*time). Regarding the profile of the mood state, the tension-anxiety domain showed a significant difference for time (p = <0.001) and interaction (p = 0.004); in the depression domain, there were also significant effects on time (p = 0.001) and interaction (p = 0.019); anger-hostility had effects on time (p = 0.030) and interaction (p = 0.042); the vigor domain did not show significant effects for the group (p = 0.075), time (p = 0.404) and interaction (p = 0.476); fatigue had an effect for time (p = 0.001) and interaction (p = 0.005); and, finally, mental confusion had a significant effect on all tested factors, namely, group (p = 0.004), time (p = 0.012), and interaction (p = 0.022). It is concluded that twelve weeks of training with a dance exergame (Dance Central 3), twice a week, lasting 50 min each session, is enough to promote improvements in the mood of untrained and supposedly healthy elderly women, with only one exception. to the vigor domain, but they were not sufficient to modify the functional fitness.